2019
DOI: 10.1177/0013124519877149
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Environmental Activism, Nonactivist Behaviors, and the Private Sphere Green Behaviors of Thai University Students

Abstract: University students are expected by the general public to be active in pro-environmental behaviors due to their environmental knowledge and relevant education. However, it is still unclear whether students only educated in environmental knowledge will decide to engage in green behaviors. This study investigates factors that determine university students’ pro-environmental behaviors, which include environmental activism, nonactivism, and private sphere environmental activities. A proposed model for investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 63 publications
0
32
0
5
Order By: Relevance
“…Nevertheless, Piyapong's (2019) findings show that males have environmental value and are more likely to engage in environmental activities at a higher level than women. The differences in these findings were influenced by environmental factors such as workload, family commitment, and knowledge of environmental issues (Levine & Strube, 2012;Piyapong, 2019). A more detailed analysis found that Male students had higher egoistic values than women.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Nevertheless, Piyapong's (2019) findings show that males have environmental value and are more likely to engage in environmental activities at a higher level than women. The differences in these findings were influenced by environmental factors such as workload, family commitment, and knowledge of environmental issues (Levine & Strube, 2012;Piyapong, 2019). A more detailed analysis found that Male students had higher egoistic values than women.…”
Section: Discussionmentioning
confidence: 86%
“…Boeve-de Pauw et al ( 2014) found that women have more pro-environmental values than men. Nevertheless, the results of Piyapong (2019) show that men have environmental value and are more likely to engage in environmental activities at a higher level than women. This reflects the value of environmental volunteerism is influenced by environmental factors such as workload, family commitment, and knowledge of environmental issues (Levine & Strube, 2012;Piyapong, 2019).…”
Section: Environmental Volunteerism Values Based On Gender and Study ...mentioning
confidence: 94%
See 2 more Smart Citations
“…The activities should be promoted to students through various environmental activities to create sustainable development. The direction of the environmental activities will lead students to understand diverse concepts of environmentally friendly cities (Cavalheiro et al, 2019;Hu & Zheng, 2020;Lodato et al, 2018;Najim & Salman, 2020;Piyapong, 2019).…”
Section: Figure 1 Causal Loop Diagram (Cld) Of Environmental Problem-...mentioning
confidence: 99%